El agroturismo como estrategia de asociatividad y revalorización sustentable de la economía en el municipio de Lejanías Meta - Franco Romero, Juana Valentina; Ospina García, Lina Marcela; Téllez Plazas, Mónica Patricia (Corporación Universitaria Minuto de Dios, 2020)
Lejanías es uno de los destinos emergentes del postconflicto, caracterizado por una economía basada en la agricultura, actualmente insuficiente debido a que no hay un valor agregado en los productos cultivados y los precios no compensan el trabajo esforzado por los campesinos. Es por esto, que fue el municipio base para la realización de esta investigación. La estrategia del proyecto radico en generar un modelo agroturístico, con el fin de determinar una manera óptima para mejorar la calidad de vida del área rural, partiendo que las tendencias buscan experiencias que llevan a viajeros a convivir con comunidades campesinas rodeados de naturaleza. A través de un modelo base, se ejemplifico una ruta agroturística inicialmente con 8 fincas, donde se entrega un mapa geográfico, un itinerario para viajeros y finqueros; además de la posibilidad de ofertar nuevos productos turísticos. Dos herramientas de comercialización, una de ellas es el pueblito campesino y otra un Eccomerce que permitirá inspirar la compra de productos agrícolas transformados. En este entender se realizó una investigación mixta, con aplicación de instrumentos como Focus Group, entrevistas, encuestas, entre otros, mediante un muestreo a conveniencia, donde intervinieron modelos agroturísticos existentes que nos determinan la aceptación del proyecto.

Lejanías is one of the emerging destinations of the post-conflict, characterized by an economy based on agriculture, currently insufficient because there is no added value in the products grown and the prices do not compensate for the hard work of the peasants. This is why it was the base municipality for the conduct of this research. The strategy of the project is to generate an agrotourism model, in order to determine an optimal way to improve the quality of life in rural areas, based on the fact that trends seek experiences that lead travelers to live with peasant communities surrounded by nature. Through a base model, an agrotourism route was exemplified initially with 8 farms, where a geographic map, an itinerary for travelers and farmers, is delivered; in addition to the possibility of offering new tourist products. Two marketing tools, one of them is the peasant town and the other an Eccomerce that will inspire the purchase of transformed agricultural products. In this understanding, a mixed investigation was carried out, with the application of instruments such as Focus Group, interviews, surveys, among others, by means of a convenience sampling, where existing agrotourism models intervened that determine the acceptance of the project.

Lejanías is one of the emerging destinations of the post-conflict, characterized by an economy based on agriculture, currently insufficient because there is no added value in the products grown and the prices do not compensate for the hard work of the peasants. This is why it was the base municipality for the conduct of this research. The strategy of the project is to generate an agrotourism model, in order to determine an optimal way to improve the quality of life in rural areas, based on the fact that trends seek experiences that lead travelers to live with peasant communities surrounded by nature. Through a base model, an agrotourism route was exemplified initially with 8 farms, where a geographic map, an itinerary for travelers and farmers, is delivered; in addition to the possibility of offering new tourist products. Two marketing tools, one of them is the peasant town and the other an Eccomerce that will inspire the purchase of transformed agricultural products. In this understanding, a mixed investigation was carried out, with the application of instruments such as Focus Group, interviews, surveys, among others, by means of a convenience sampling, where existing agrotourism models intervened that determine the acceptance of the project.
Diseñar un modelo en Agroturismo como estrategia encaminada al Turismo Comunitario buscando la revalorización sustentable para el mejoramiento de las condiciones de vida de los campesinos del Municipio de Lejanías en el departamento del Meta (2020).
Keywords: Agroturismo; Cadena de valor; asociatividad; economía campesina; Agrotourism; value chain; associativity; peasant economy; peasant economy